A novel zinc based binary catalytic system for CO2utilization under mild conditions - Desens, Willi; Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Organic Chemistry Frontiers)
A novel zinc based binary catalytic system for the synthesis of cyclic carbonates under mild and solvent-free conditions utilizing CO2as a C1 building block is reported.
Keywords: Organic Chemistry

Novel Base-Free Catalytic Wittig Reaction for the Synthesis of Highly Functionalized Alkenes - Schirmer, Marie-Luis; Adomeit, Sven; Spannenberg, Anke; Werner, Thomas (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Regio- and Stereoselective Synthesis of Dithiocarbonates under Ambient and Solvent-Free Conditions - Diebler, Johannes; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Convergent Activation Concept for CO2Fixation in Carbonates - Desens, Willi; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Atom economical synthesis of di- and trithiocarbonates by the lithium tert-butoxide catalyzed addition of carbon disulfide to epoxides and thiiranes - Diebler, J.; Spannenberg, A.; Werner, Thomas (Organic and Biomolecular Chemistry)
The lithium tert-butoxide catalyzed addition of CS2 to epoxides and thiiranes under mild conditions is reported. A mechanism has been proposed taking into account the regio- and stereochemical outcome of the reaction.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Cooperative catalyst system for the synthesis of oleochemical cyclic carbonates from CO2and renewables - Tenhumberg, Nils; Büttner, Hendrik; Schäffner, Benjamin; Kruse, Daniela; Blumenstein, Michael; Werner, Thomas (Green Chemistry)
Taking Control!The binary catalyst system composed of MoO3and an organic phoshponium salt [Bu4P]X proved very efficient to produce oleochemical cyclic carbonates from renewables.
Keywords: Pollution; Environmental Chemistry

Alkoxide-Initiated Regioselective Coupling of Carbon Disulfide and Terminal Epoxides for the Synthesis of Strongly Alternating Copolymers - Diebler, Johannes; Komber, Hartmut; Häußler, Liane; Lederer, Albena; Werner, Thomas (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Iron-Based Binary Catalytic System for the Valorization of CO2 into Biobased Cyclic Carbonates - Büttner, Hendrik; Grimmer, Christoph; Steinbauer, Johannes; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Organocatalyzed Synthesis of Oleochemical Carbonates from CO2and Renewables - Büttner, Hendrik; Steinbauer, Johannes; Wulf, Christoph; Dindaroglu, Mehmet; Schmalz, Hans-Günther; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Aufklärung und Imagination in Frankreich (1675-1810) - Anthologie und Analyse.

Cover Picture: Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence (Adv. Synth. Catal. 23/2016) - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)
Keywords: General Chemistry

Cycloisomerisierung von 1,5-Eninen über eine 5-endo-dig- Cyclisierungs-Protodeborylierungs-Sequenz mit einem frustrierten Lewis-Paar als Katalysator - Tamke, Sergej; Qu, Zheng-Wang; Sitte, Nikolai A.; Flörke, Ulrich; Grimme, Stefan; Paradies, Jan (Angewandte Chemie)

Cover Picture: Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence (Adv. Synth. Catal. 23/2016) - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)

Frustrated Lewis Pair Catalyzed Dehydrogenative Oxidation of Indolines and Other Heterocycles - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Dehydrierende Oxidation von Indolinen und anderen Heterocyclen durch frustrierte Lewis-Paare - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie)

Frustrated Lewis Pair-Catalyzed Cycloisomerization of 1,5-Enynes via a 5-endo-dig Cyclization/Protodeborylation Sequence - Tamke, Sergej; Qu, Zheng-Wang; Sitte, Nikolai A.; Flörke, Ulrich; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Frustrated Lewis Pair Catalyzed Dehydrogenative Oxidation of Indolines and Other Heterocycles - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)

Structure-Reactivity Relationship in the Frustrated Lewis Pair (FLP)-Catalyzed Hydrogenation of Imines - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry - A European Journal)

Heteroacene Synthesis through C−S Cross-Coupling/5-endo-digCyclization - Oechsle, Peter; Flörke, Ulrich; Egold, Hans; Paradies, Jan (Chemistry - A European Journal)

Inside Cover: Structure–Reactivity Relationship in the Frustrated Lewis Pair (FLP)‐Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Inside Cover: Structure-Reactivity Relationship in the Frustrated Lewis Pair (FLP)-Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry - A European Journal)

The concept of generalized stresses for computational manufacturing and beyond - Mahnken, Rolf; Cheng, Chun; Düsing, Martin; Ehlenbröker, Ulrich; Leismann, Thorben (GAMM-Mitteilungen)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Lehrbuch der Technischen Mechanik - Band 1: Starrkörperstatik - Mahnken, Rolf

Temperature-insensitive electro-optic response of polymer-stabilized blue phases - Nordendorf, Gaby; Schmidtke, Jürgen; Wilkes, David; Kitzerow, Heinz-Siegfried (Journal of Materials Chemistry C)
Polymer-stabilized blue phase liquid crystal in-plane switching cell.
Keywords: Materials Chemistry; General Chemistry

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Integral representation and sharp asymptotic results for some Heckman-Opdam hypergeometric functions of type BC - Rösler, Margit; Voit, Michael (Transactions of the American Mathematical Society)

A multivariate version of the disk convolution - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Time-Resolved Mueller Matrix Measurement and Polarization Scrambler Characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Erklärungsfaktoren für Einstellungen von Schülerinnen und Schülern im Grundschulalter gegenüber Kindern mit sonderpädagogischem Förderbedarf – Ergebnisse aus einer empirischen Studie. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Leistungsrückmeldungen im Zusammenhang mit Leseleistungen, Selbstwirksamkeitsüberzeugungen und Kausalattributionen bei Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Ort, Margarita; Hellmich, Frank

Prädiktoren für Einstellungen und Motivation bei Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf den inklusiven Unterricht. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Görel, Gamze; Hellmich, Frank

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Förderung inklusiven Lernens im naturwissenschaftlich-technischen Sachunterricht der Grundschule. Vortrag auf der 4. Jahrestagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Blumberg, Eva; Fromme, Theresa; Hellmich, Frank

Zur Feinstaubabscheidung aus Holzfeuerungsanlagen mit precoatierten Oberflächenfiltern - Schiller, Sascha

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Kinder mit Lernschwierigkeiten in der Grundschule - Miller, Susanne; Kottmann, Brigitte (Differenz - Ungleichheit - Erziehungswissenschaft)

"Und dann war das auch noch so ein kleines, zartes Persönchen": Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Miller, Susanne; Kottmann, Brigitte (Diagnostik im Kontext inklusive Bildung)

Selektion inklusive?! Widersprüche bei der umsetzung von Inklusion in der Schule - Kottmann, Brigitte; Miller, Susanne (Empirische Forschung im Kontext Schule)

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

In-lab ALOHA mid-infrared up-conversion interferometer with high fringe contrast @λ = 3.39 μm - Szemendera, L.; Darré, P.; Baudoin, R.; Grossard, L.; Delage, L.; Herrmann, Harald; Silberhorn, Christine; Reynaud, F. (Monthly Notices of the Royal Astronomical Society)
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

Bayesian Information Criterion for Source Enumeration in Large-Scale Adaptive Antenna Array - Huang, Lei; Xiao, Yu-Hang; Liu, Kefei; So, Hing Cheung; Zhang, Jian-Kang (IEEE Transactions on Vehicular Technology)

Shrinkage of covariance matrices for linear signal estimation using cross-validation - Tong, Jun; Schreier, Peter J.; Guo, Qinghua; Tong, S.; Xi, Jiangtao; Yu, Y. (IEEE Trans.\ Signal\ Process.)

DOA parameter estimation with 1-bit quantization - Bounds, methods and the exponential replacement - Stein, Manuel; Barbé, Kurt; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Asymptotic performance analysis for $1$-bit Bayesian smoothing - Zhang, Lin; Stein, Manuel; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Performance analysis for pilot-based $1$-bit channel estimation with unknown quantization threshold - Stein, Manuel; Bar, Shahar; Nossek, Josef A.; Tabrikian, Joseph (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Choosing the diagonal loading factor for linear signal estimation using cross validation - Tong, Jun; Guo, Qinghua; Xi, Jiangtao; Yu, Y.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Adaptive visual sort and summary of micrographic images of nanoparticles for forensic analysis - Jurrus, Elizabeth; Hodas, Nathan; Baker, Nathan; Marrinan, Tim; Hoover, Mark D (Technologies for Homeland Security (HST), 2016 IEEE Symposium on)

Accurate Asymptotic Analysis for Johns Test in Multichannel Signal Detection - Xiao, Y-.H.; Huang, L.; Xie, J.; H. C. So, and (Proc. IEEE Int. Conf. Acoust., Speech, Signal Process. (ICASSP))

Canonical correlation analysis of high-dimensional data with very small sample support - Song, Yang; Schreier, Peter J.; Ramírez, David; Hasija, Tanuj (Signal Process.)

Detecting the dimension of the subspace correlated across multiple data sets in the sample poor regime - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ IEEE Work.\ Stat.\ Signal Process.)

Bootstrap-based detection of the number of signals correlated across multiple data sets - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ Asilomar Conf.\ Signals\ Syst. Computers)

Determining the number of signals correlated across multiple data sets for small sample support - Song, Yang; Hasija, Tanuj; Schreier, Peter J.; Ramírez, David (Proc.\ Eur.\ Signal Process.\ Conf.)

Reflexionen des Technischen zwischen Überleben und gutem Leben - Alpsancar, Suzana (Jahrbuch Technikphilosophie 2016. List und Tod)

Natur - Alpsancar, Suzana (Professionell Ethik und Philosophie unterrichten: Ein Arbeitsbuch)

Pollution Control Meets Sustainability: Structure-Activity Studies on New Iron Oxide-Based CO Oxidation Catalysts - Schoch, Roland; Bauer, Matthias (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Interkorporalität - Haller, Melanie; Klein, Gabriele; Meuser, Michael; Gugutzer (Hg.), Robert (Handbuch Körpersoziologie. Körpersoziologische Grundbegriffe und theoretische Perspektiven, Wiesbaden 2016.)

Salsa - Hartmann, Annette; Woitas, Monika; Haller, Melanie (Das große Tanzlexikon. Personen, Werke, Tanzkulturen, Epochen, Laaber: Laaber 2016, S. 530-531.)

Swing - Haller, Melanie; Hartmann, Annette; Woitas, Monika (Das große Tanzlexikon. Personen, Werke, Tanzkulturen, Epochen, Laaber: Laaber 2016.)

Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

Molecular dynamics and reverse Monte Carlo modeling of scheelite-type AWO4(A = Ca, Sr, Ba) WL3-edge EXAFS spectra - Kalinko, Aleksandr; Bauer, Matthias; Timoshenko, Janis; Kuzmin, Alexei (Physica Scripta)
Keywords: Condensed Matter Physics; Mathematical Physics; Atomic and Molecular Physics; and Optics

Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.

Integrative Verknüpfung von Studium und Praxis am Leuphana College. - Hellmann, Karina; Teigeler, Mareike; Seifert, Andreas (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

“Und sie bewegt sich doch!” – Wie spezifische Lerngelegenheiten die bildungswissenschaftlichen Kompetenzen von Lehramtsstudierenden fördern können. - Plöger, Wilfried; Scholl, Daniel; Seifert, Andreas (Zeitschrift für Pädagogik)

Universitäre Bildung und Hochschule im Wandel – das Beispiel Leuphana Universität Lüneburg. - Schütz, Julia; Seifert, Andreas; Gunkel, Marjaana (Das Hochschulwesen)

Smale-Scale-Assessments in den Bildungswissenschaften. - Lüders, Manfred; Seifert, Andreas (Lehrerbildung auf dem Prüfstand)

Preschoolers’ engagement in social interaction with an autonomous robotic system. - Lücking, Philipp; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (Proceedings of the IEEE ICDL-EpiRob 2016)

Vocal interactions at the dawn of communication: The emergence of mutuality and complementarity in mother-infant interaction. - Leonardi, Giuseppe; Nomikou, Iris; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna (Proceedings of the IEEE ICDL-EpiRob 2016)

Pragmatic Frames for Teaching and Learning in Human–Robot Interaction: Review and Challenges - Vollmer, Anna-Lisa; Wrede, Britta; Rohlfing, Katharina; Oudeyer, Pierre-Yves (Frontiers in Neurorobotics)

Language meddles with infants‘ processing of observed actions - Sciutti, Alessandra; Lohan, Katrin Solveig; Gredebäck, Gustaf; Koch, Benjamin; Rohlfing, Katharina (Frontiers in Robotics and AI)

Language—at all times. Action and interaction as contexts for enriching representations. - Nomikou, Iris; Malte, Schilling; Heller, Vivien; Rohlfing, Katharina (Interaction Studies)

Die KOMFOR-Studie zum studentischen Wahlverhalten in überfachlichen Studienprogrammen – statistische Analysen und Auswertung von Interviews. - Strunz, Cathleen; Adomßent, Maik; Seifert, Andreas; Schütz, Julia; Gunkel, Marjaana (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

Embodied Language Learning and Cognitive Bootstrapping: Methods and Design Principles - Lyon, Caroline; Nehaniv, Chrystopher L.; Saunders, Joe; Belpaeme, Tony; Bisio, Ambra; Fischer, Kerstin; Forster, Frank; Lehmann, Hagen; Metta, Giorgio; Mohan, Vishwanathan; Morse, Anthony; Nolfi, Stefano; et al. (International Journal of Advanced Robotic Systems)
Co-development of action, conceptualization and social interaction mutually scaffold and support each other within a virtuous feedback cycle in the development of human language in children. Within this framework, the purpose of this article is to bring together diverse but complementary accounts of research methods that jointly contribute to our understanding of cognitive development and in particular, language acquisition in robots. Thus, we include research pertaining to developmental robotics, cognitive science, psychology, linguistics and neuroscience, as well as practical computer science and engineering. The different studies are not at this stage all connected into a cohesive whole; rather, they are presented to illuminate the need for multiple different approaches that complement each other in the pursuit of understanding cognitive development in robots. Extensive experiments involving the humanoid robot iCub are reported, while human learning relevant to developmental robotics has also contributed useful results. Disparate approaches are brought together via common underlying design principles. Without claiming to model human language acquisition directly, we are nonetheless inspired by analogous development in humans and consequently, our investigations include the parallel co-development of action, conceptualization and social interaction. Though these different approaches need to ultimately be integrated into a coherent, unified body of knowledge, progress is currently also being made by pursuing individual methods.
Keywords: Robot Language; Human Robot Interaction; HRI; Developmental Robotics; Cognitive Bootstrapping; Statistical Learning

Effekte von Objekt-Familiarisierung auf die frühe gestische Kommunikation. Individuelle Unterschiede in Hinblick auf den späteren Wortschatz - Grimminger, Angela; Lüke, Carina; Ritterfeld, Ute; Liszkowski, Ulf; Rohlfing, Katharina (Frühe Bildung)
There is ongoing discussion on the function of the early production of gestures with regard to whether they reduce children's cognitive demands and free their capacity to perform other tasks (e.g., Goldin-Meadow & Wagner, 2005) or whether young children point in order to share their interest or to elicit information from their caregivers (e.g., Begus & Southgate, 2012; Liszkowski, Carpenter, Henning, Striano & Tomasello, 2004). The different assumptions lead to diverse predictions regarding infants' gestural or multimodal behavior in recurring situations, in which some objects are familiar and others are unfamiliar. To examine these different predictions, we observed 14 children aged between 14 and 16 months biweekly in a semi-experimental situation with a caregiver and explored how children's verbal and gestural behaviors change as a function of their familiarization with objects. We split the children into two groups based on their reported vocabulary size at 21 months of age (larger vs. smaller vocabulary). We found that children with a larger vocabulary at 21 months had an increase in their pointing with words toward unfamiliar objects as well as in their total amount of words, whereas for children with smaller vocabularies we did not find differences in relation to their familiarization with objects. We discuss these findings in terms of a social-pragmatic use of pointing gestures.
Keywords: gesture; pointing; familiarity; individual differences

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Preschoolers' engagement in social interaction with an autonomous robotic system - Lücking, Phillip; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (2016 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob))

Einstellungen zur Inklusion im Zusammenhang mit der Motivation für die Beschäftigung mit inklusionsspezifischen Fragestellungen bei Studentinnen und Studenten des Lehramts an Grundschulen. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Görel, Gamze; Hellmich, Frank; Schwab , Susanne

Rückmeldungen zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hellmich, Frank; Hoya, Fabian Karl

Einstellungen zum inklusiven Unterricht bei Lehrkräften als Voraussetzungen für inklusives Lernen in der Grundschule. Vortrag auf dem 25. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank

Primary school children`s attitudes towards peers with special educational needs - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Primary school teachers` attitudes towards inclusion and their interest in inclusive teaching - Görel, Gamze; Hellmich, Frank

Leseleistungen von Kindern im Grundschulalter im Zusammenhang mit den Rückmeldungen ihrer Lehrerinnen und Lehrer im Leseunterricht der Grundschule – Ergebnisse aus einer Mehrebenenanalyse. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hoya, Fabian Karl; Hellmich, Frank

Motivation und Einstellungen zur Inklusion bei deutschen und österreichischen Studentinnen und Studenten mit dem Studienschwerpunkt Grundschule – ein Vergleich. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank; Schwab, Susanne

Bedingungsfaktoren für Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

The role of pre-service teachers` attitudes towards inclusion for their motivation to engage in inclusive educational issues during their studies. Vortrag im Rahmen des Symposiums "Teachers' self-efficacy beliefs, attitudes and motivation to engage in inclusive education" (Chair: Marco Hessels). ECER 2016 (European Conference on Educational Research) - Hellmich, Frank; Görel, Gamze; Schwab, Susanne

The role of primary school students`perceptions of their parental and teachers` feedback for their reading motivation. Vortrag auf der ECER 2016 (European Conference on Educational Research). „Leading Education: The Distinct Contributions of Educational Research and Researchers" - Hoya, Fabian Karl; Hellmich, Frank

Towards a quantum interface between telecommunication and UV wavelengths: design and classical performance - Rütz, Helge; Luo, Kai-Hong; Suche, Hubertus; Silberhorn, Christine (Applied Physics B)

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Hardy–Stein identities and square functions for semigroups - Bañuelos, Rodrigo; Bogdan, Krzysztof; Luks, Tomasz (Journal of the London Mathematical Society)
Keywords: General Mathematics

Kohäsion und soziales Kapital : Ausschließungsprozesse in der Sozialen Arbeit - Landhäußer, Sandra (Sozialmagazin)
Soziale Arbeit rückt im Zusammenhang mit der Thematisierung eines geringen gesellschaftlichen Zusammenhalts in den Vordergrund, wenn vermehrte Kohäsion mit der Aktivierung sozialen Kapitals erreicht werden soll. Vor diesem Hintergrund wird eine auf politischer Ebene prominente Version sozialen Kapitals sowie ihr Beitrag zur Erhöhung gesellschaftlichen Zusammenhalts genauer untersucht und auf seine Aussagekraft für die Soziale Arbeit hin befragt.

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg